Analisis Desain Pemasangan Ulang Hydraulic Pumping Unit Dalam Mengoptimalkan Laju Produksi Pada Sumur “AGT” Lapangan “Tiku Kalua” - Aprilia Gabriela Tiku; Engeline Malrin; Esterina Natalia Paindan; Mohammad Lutfi; Abdul Gafar Karim; Khusnul Hotimah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2022)
The “AGT” well in the “Tiku Kalua” field is a new producing well using an artificial lift, particulary an electric submersible pump (ESP), but due to the use of ESP it cannot provide optimal results as expected in the “AGT” well, and if a redesign is carried out on the ESP to increase the flow rate (Q) will cause formation damage so than an artificial lift is re-selected according to the well conditions, based on artificial lift screening that meets the criteria is a hydraulic pumping unit (HPU). In the “AGT” well, an artificial lift design with a hydraulic pumping unit (HPU) type to optimize the production rate using the single-phase IPR. The purpose of this final project research is to determine a safe HPU design to optimize producing rate . Based on the result ofs the analysis of the “AGT” well, it has a PI value of 0,108 bbl/psi, Qmax 86,252 bfpd, pump size (plunger) 2 in, combined rod size 5/8 and ½ in, the pumping speed (N) 4.2 SPM, pump stroke length (S) 58 in at a production rate (Q) of 76,9 bfpd. Smax 14,013.45 psi, Smin 3,687.11 psi and stress available 23,218.85 where (SA≥Smax) so that the design is safe enough to withstand maximum loads.